Necrosectomía laparoscópica en pancreatitis aguda - RICARDO FUNKE H. (Revista Chilena de Cirugía, 2010)
Laparoscopic surgery can be used in the treatment of severe acute pancreatitis. Aim: To report the experience with laparoscopic necrosectomy and abscess drainage in severe acute pancreatitis. Material and Methods: Retrospective analysis of medical records of 11 patients aged 13 to 78 years (10 males), with severe pancreatitis, subjected to laparoscopic necrosectomy or abscess drainage between 2006 and 2009. Results: Operative time ranged from 110 to 205 min. In all cases, a satisfactory necrosectomy and collection drainage were performed. No complications were recorded and no patient required to be converted to open surgery. Five patients were reoperated. In three of these, the laparoscopic approach was used again. Conclusions: Laparoscopic necrosectomy is safe and useful for patients with severe pancreatitis.